Secure power management strategy for direct torque controlled fuel cell/ supercapacitor electric vehicles - Oubelaid, Adel; Taib, Nabil; Rekioua, Toufik; Bajaj, Mohit; Yadav, Arvind; Shouran, Mokhtar; Kamel, Salah (Frontiers in Energy Research, 2022)
High reliability is recommended in hybrid electric vehicle applications. In this study, a secure power management strategy has been developed for a fuel cell—supercapacitor hybrid electric vehicle. In addition to its ability to detect the occurrence of failures in vehicle power sources, the proposed power management strategy isolates the faulty source and reconfigures the control scheme to always guarantee bus voltage stability and vehicle traction even in faulty situations. The developed power management strategy enhances vehicle comfort and prevents exhausting one source over another by allowing the fuel cell and the supercapacitor to operate at different power levels. The multiloop control scheme associated with the power sources is highly reliable since both sources can run the vehicle alone and regulate the bus voltage. Vehicle speed and torque controllers are simultaneously tuned using a particle swarm optimization algorithm. Torque and speed ripples are automatically minimized via the use of a new proposed cost function. This approach made the controller design easier and gave the designer the possibility to tradeoff between the variables to be minimized.